2014
DOI: 10.1002/cncr.28593
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cytoskeleton‐associated membrane protein 4 and its palmitoyl acyltransferase DHHC2 in hepatocellular carcinoma

Abstract: BACKGROUND:The functions of cytoskeleton-associated membrane protein 4 (CKAP4), one kind of type II transmembrane protein, are associated with the palmitoyl acyltransferase DHHC2. The objective of the current study was to investigate CKAP4=DHHC2 expression and its prognostic significance in patients with hepatocellular carcinoma (HCC). METHODS: Two independent cohorts of 416 patients with HCC were enrolled. All the patients included had defined clinicopathologic and follow-up data. Using real-time polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…All four datasets showed consistent results, indicating that CKAP4 mRNA levels were significantly higher in tumor tissues compared with adjacent liver tissues. These results confirm the upregulation of CKAP4 in tumor tissues in accordance with previous results found in HCC (19) and other types of cancer, including cervical cancer, bladder cancer, lung cancer, pancreatic cancer, ESCC, CLL, PDAC and intrahepatic cholangiocellular carcinoma (12)(13)(14)(15)(16)(17)(18)27).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All four datasets showed consistent results, indicating that CKAP4 mRNA levels were significantly higher in tumor tissues compared with adjacent liver tissues. These results confirm the upregulation of CKAP4 in tumor tissues in accordance with previous results found in HCC (19) and other types of cancer, including cervical cancer, bladder cancer, lung cancer, pancreatic cancer, ESCC, CLL, PDAC and intrahepatic cholangiocellular carcinoma (12)(13)(14)(15)(16)(17)(18)27).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, exosomal CKAP4 was reported to be a promising biomarker for pancreatic ductal adenocarcinoma (PDAC) (18). In 2013, Li et al (19) first revealed that CKAP4 was associated with progression and metastasis in patients with HCC. CKAP4 expression was demonstrated to be significantly higher in HCC tissues compared with adjacent normal tissues, and was associated with tumor size, intrahepatic metastasis, portal venous invasion and tumor stage; furthermore, upregulated CKAP4 expression increased overall survival (OS) and disease-free survival (DFS) times in patients with HCC.…”
Section: Cytoskeleton-associated Membrane Protein 4 Is Upregulated Inmentioning
confidence: 99%
“…transition from the precancerous state to the cancerous state. However, it was reported that high expression of CKAP4 is correlated with longer overall survival in cholangiocarcinoma and hepatocellular carcinoma patients (48,49), although the expression levels of DKK1 were not examined in these cases. CKAP4 might function in a positive or negative role for cellular proliferation in cancer contexts.…”
Section: Ckap4 Functions As a Novel Receptor For Dkk1 And Mediates Dkmentioning
confidence: 99%
“…There are opposing reports for intrahepatic cholangiocarcinoma (ICC) and HCC (Li et al, ; Li et al, ). CKAP4 expression is associated with tumour size and lymph node metastasis of ICC, but CKAP4 is expressed less in lymph node metastatic lesions rather than in primary lesions.…”
Section: Ckap4 Expression Is Related With Prognosis Of Cancer Patientsmentioning
confidence: 99%